High-temperature-resistant and low-temperature-resistant elastic cable material as well as preparation method and application thereof in cable
By adding specific components and dynamic vulcanization processes to the cable material, a micro-phase separation structure is formed, which solves the problem of insufficient performance of traditional cable material in extreme high and low temperature environments, and improves high temperature stability, low temperature flexibility and anti-aging performance, and is suitable for new energy vehicles and polar scientific research fields.
Patent Information
- Application Number
- CN202510664702.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-08-01
Smart Images

Figure CN120399388A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and specifically to a high-temperature and low-temperature resistant elastic cable material, its preparation method, and its application in cables. Background Art
[0002] With the rapid development of new energy vehicles, aerospace, and polar scientific research, etc., the performance requirements for cable materials are becoming increasingly stringent. The performance defects of traditional cable materials in extreme high and low temperature environments are becoming more and more obvious, specifically manifested as follows: Insufficient high-temperature resistance: The long-term service temperature of conventional PVC cables generally does not exceed 105°C, the upper temperature limit of EPDM is about 150°C, and it is prone to softening and deformation in high-temperature environments, resulting in deterioration of insulation performance and unable to meet the requirements of electric vehicle charging piles and industrial robot joint wire harnesses; Poor low-temperature resistance: The low-temperature embrittlement temperature of PVC and CR materials is usually higher than -40°C, and it is prone to brittle fracture in extremely cold environments, resulting in cracking of the cable sheath and exposure of the conductor, seriously affecting the safe operation of equipment; Weak anti-aging performance: After high-temperature aging, the material is prone to oxidative degradation, and the mechanical properties are significantly reduced, unable to meet the requirements of long-term stable operation of industrial equipment. Summary of the Invention
[0003] Therefore, the present invention provides a high-temperature and low-temperature resistant elastic cable material, its preparation method, and its application in cables to solve the above problems.
[0004] The present invention provides the following technical solution: A high-temperature and low-temperature resistant elastic cable material, including cable material, the composition of the cable material contains Kraton G1650, the composition of the cable contains polyether TPU, the composition of the cable contains modified nano-silica, the composition of the cable contains montmorillonite complex, the composition of the cable contains BASF Tinuvin770, the composition of the cable contains paraffin oil, the composition of the cable contains antioxidant 1010, and the ratio of Kraton G1650, polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin770, paraffin oil and antioxidant 1010 is 35:25:3:2:0.5:15:0.2.
[0005] A preparation method of a high-temperature and low-temperature resistant elastic cable material, using a high-temperature and low-temperature resistant elastic cable material, includes the following steps: Step 1, mixing; Step 2, extrusion; Step 3, vulcanization; Step 4, testing.
[0006] As a preferred embodiment of the present invention, in Steps 1 to 4, more specifically: in the mixing step, except for the antioxidant, Kraton G1650, polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin770 and paraffin oil are dried in a vacuum drying oven at 120 °C for 4 hours to remove moisture and low molecular weight volatiles, and then mixed at room temperature for 15 minutes using a high-speed mixer to ensure nano-level uniform dispersion, and the particle size distribution D90 / D10 ≤ 5 is detected by a laser particle size analyzer; In the extrusion step, the premix is added to an extruder. The temperature gradient of the 120 mm twin-screw extruder is controlled as follows: from 170 °C in Zone 1 to 180 °C in Zone 2 to 190 °C in Zone 3 to 200 °C in Zones 4 to 9 to 210 °C in Zone 10. The twin-screw rotation speed is 300 rpm, the length-diameter ratio L / D ≥ 48:1, the vacuum degree ≤ -0.09 MPa for devolatilization, the melt pressure is 5 - 10 MPa, the die head temperature is 220 °C, and the residence time is 4 - 6 minutes; In the vulcanization step, a dynamic vulcanization process is implemented at the die orifice of the extruder. The vulcanization temperature is 220 °C, the die orifice pressure is 8 MPa, and the residence time is 5 minutes to form a microphase separation structure; In the testing step, after molding, the cable material is granulated by water ring cutting or calendered by a granulator, and the performance is detected according to the following standards: Tensile properties: Detected by ASTM D412-22, the test standards are: elongation at break > 350%, tensile strength > 28 MPa; Low-temperature brittleness: Detected by GB / T 2951.4, the test standard is: embrittlement temperature < -50 °C; Thermal aging properties: Detected by IEC 60216-1, the test standard is: the performance retention rate > 88% after 150 °C x 168 h; Electrical insulation properties: Detected by GB / T 3048-2007, the test standard is: volume resistivity > 1014 Ω·cm.
[0007] The application of a high-temperature and low-temperature resistant elastic cable material in a cable, using any one of the high-temperature and low-temperature resistant elastic cable materials and a preparation method of a high-temperature and low-temperature resistant elastic cable material. The cable material is used to manufacture the sheath layer or insulation layer of a high-temperature and low-temperature resistant cable, and is suitable for high and low temperature environments in fields such as industrial robots, new energy vehicles, and polar scientific research; The cable compound forms a microphase-separated structure through a dynamic vulcanization process, where the styrene block serves as a permanent physical crosslinking point, inhibiting the softening flow caused by chain segment migration and ensuring the structural stability of the cable under long-term operation scenarios at 150 - 200 °C. It is applicable to the wire harnesses of electric vehicle charging piles and at the joints of industrial robot wire harnesses. The antioxidant 1010 and the phosphite auxiliary antioxidant 168 are compounded to inhibit the molecular chain breakage induced by high-temperature oxidation through the dual mechanisms of hydroperoxide decomposition and free radical chain termination. After thermal aging at 150 °C for 168 h, the property retention rate is > 88%; In Kraton G1650, a styrene-butadiene-styrene copolymer and a polyether TPU are blended to form a multiphase elastomer network, where the proportion of the TPU soft segment is 25%, ensuring that the material does not crack under low-temperature impact at -70 °C. It is applicable to the cables of polar scientific research equipment. The phosphite antioxidant 168 restricts the low-temperature crystallization tendency of the polyether TPU molecular chain through free radical capture, maintaining the low-temperature resilience and elongation at break of the material; In the composition of the cable compound, a composite antistatic agent and a montmorillonite complex are added to form a surface charge dissipation channel, reducing the surface resistance and preventing insulation failure caused by local electric field distortion.
[0008] As a preferred embodiment of the present invention, the surface of the cable compound has antistatic properties.
[0009] As a preferred embodiment of the present invention, the modified nano-silica is surface-grafted with polyacrylate through a silane coupling agent, the grafting rate of the modified nano-silica is ≥ 90%, the thickness of the hexagonal boron nitride nanosheets in the montmorillonite complex is < 5 nm, the aspect ratio of the montmorillonite in the montmorillonite complex is > 50, the hexagonal boron nitride nanosheets and the montmorillonite are compounded by a mechanochemical method, the temperature of the screw in the extruder is gradually increased in sections, reducing the accumulation of shear heat and avoiding material thermal degradation. An on-line viscometer and a laser particle size analyzer are configured during the extrusion process of the extruder to provide real-time feedback on the fluidity and dispersion state of the material.
[0010] As a preferred embodiment of the present invention, the modified nano-silica is grafted in an ethanol solvent through a silane coupling agent KH-550, the mass ratio of KH-550 to silica is 1:5, after grafting, the modified nano-silica is dried at 60 °C to remove the solvent, and the grafting rate of the modified nano-silica is 290%; The hexagonal boron nitride nanosheets and sodium-based montmorillonite are mixed in a ratio of 2:3 and compounded by a mechanochemical method using a high-speed ball mill, with a particle size D50 < 1 μm and uniform dispersion.
[0011] Compared with the prior art, the beneficial effects of the present invention are: In the present invention, through multi-scale component design (SBS / TPU blend network, nano-filler modification), optimization of the dynamic vulcanization process, and the synergistic effect of the anti-aging system, the cable compound achieves breakthroughs in comprehensive performance, including a wide temperature range (-70°C to 200°C), high anti-aging performance (the performance retention rate at 150°C for 168 hours is 92%), antistatic property, and high thermal conductivity (4.2 W / m·K). The innovation of its principle is reflected in: the microphase separation structure inhibits softening and flow, KH-550 grafting improves dispersibility and mechanical properties, the synergistic inhibition of aging by free radical capture and peroxide decomposition, and the improvement of stability by online monitoring and segmented temperature control. This technology breaks through the performance limits of traditional cable compounds and is applicable to harsh working conditions such as electric vehicle charging piles and industrial robots. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a schematic diagram of the composition of the cable compound of the present invention; Figure 2 It is a flow chart of the preparation method of the cable compound of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0013] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0014] Please refer to Figure 1 - Figure 2 , the technical solutions provided by the present invention specifically include the following embodiments: Embodiment: A high-temperature and low-temperature resistant elastic cable compound, including a cable compound. The composition of the cable compound contains Kraton G1650, the composition of the cable contains polyether TPU, the composition of the cable contains modified nano-silica, the composition of the cable contains a montmorillonite complex, the composition of the cable contains BASF Tinuvin770, the composition of the cable contains paraffin oil, and the composition of the cable contains antioxidant 1010. The ratio of Kraton G1650, polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin770, paraffin oil, and antioxidant 1010 is 35:25:3:2:0.5:15:0.2; Kraton G1650 is a styrene-butadiene-styrene block copolymer, polyether TPU is a thermoplastic polyurethane, the modified nano-silica is grafted with KH-550 silane coupling agent, and the grafting rate is 90%. The montmorillonite complex is a mixture of hexagonal boron nitride nanosheets (thickness <5 nm) and sodium montmorillonite (aspect ratio >50) in a ratio of 2:3, ball-milled and compounded. BASF Tinuvin770 is an ultraviolet absorber.
[0015] A preparation method of a high-temperature and low-temperature resistant elastic cable material, using a high-temperature and low-temperature resistant elastic cable material, includes the following steps: Step 1, mixing: Place Kraton G1650, polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin770, and paraffin oil in a vacuum drying oven at 120°C for 4 hours to remove moisture and low-molecular volatile substances. Then use a high-speed mixer to mix at room temperature for 15 minutes. The particle size distribution of the mixed material is detected by a laser particle size analyzer, and D90 / D10 = 3.2 (meeting the requirement of ≤5). Step 2, extrusion: Add the premixed material to a 120mm twin-screw extruder. The temperature gradient is as follows: zone 1 at 170°C → zone 2 at 180°C → zone 3 at 190°C → zones 4 to 9 at 200°C → zone 10 at 210°C. The twin-screw speed is 300 rpm, L / D = 52:1, the vacuum degree ≤ -0.09 MPa, the melt pressure is 8 MPa, the die head temperature is 220°C, and the residence time is 5 minutes. Step 3, vulcanization: Implement dynamic vulcanization at the die orifice of the extruder. The vulcanization temperature is 220°C, the die orifice pressure is 8 MPa, and the residence time is 5 minutes to form a microphase separation structure. Step 4, testing: After water ring pelletization, calender and form, and sample to test the performance.
[0016] In steps 1 to 4, more specifically: In the mixing step, except for the antioxidant, place Kraton G1650, polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin770, and paraffin oil in a vacuum drying oven at 120°C for 4 hours to remove moisture and low-molecular volatile substances. Then use a high-speed mixer to mix at room temperature for 15 minutes to ensure nano-level uniform dispersion, and detect the particle size distribution D90 / D10 ≤ 5 by a laser particle size analyzer. In the extrusion step, add the premixed material to the extruder. The temperature gradient of the 120mm twin-screw extruder is controlled as follows: zone 1 at 170°C to zone 2 at 180°C to zone 1 at 190°C to zones 4 to 9 at 200°C to zone 10 at 210°C. The twin-screw speed is 300 rpm, the length-diameter ratio L / D ≥ 48:1, the vacuum degree ≤ -0.09 MPa for devolatilization, the melt pressure is 5 - 10 MPa, the die head temperature is 220°C, and the residence time is 4 - 6 minutes. In the vulcanization step, implement a dynamic vulcanization process at the die orifice of the extruder. The vulcanization temperature is 220°C, the die orifice pressure is 8 MPa, and the residence time is 5 minutes to form a microphase separation structure. In the testing step, after the formed cable material is water ring pelletized or calendered by a granulator, test the performance according to the following standards: Tensile properties: Detect by ASTM D412 - 22. The test standard is: elongation at break > 350%, tensile strength > 28 MPa; Low-temperature brittleness: Detected by GB / T 2951.4, the test standard is: embrittlement temperature < -50°C; Thermal aging performance: Detected by IEC60216-1, the test standard is: performance retention rate > 88% after 150°C x 168h; Electrical insulation performance: Detected by GB / T 3048-2007, the test standard is: volume resistivity > 10^14 Ω·cm; According to the above steps, comparisons of different formulations are carried out, including the following comparison groups; Comparison group 1: Reduce polyether TPU to 15% (original 25%), and the rest of the formulation remains unchanged; Comparison group 2: Reduce modified nano-silica to 1% (original 3%), and the rest of the formulation remains unchanged; Example group (the present invention): Maintain the original formulation (mixing ratio 35:25:3:2:0.5:15:0.2); Conclusion: Reducing TPU leads to a decrease in low-temperature toughness, and reducing silica leads to deterioration of heat aging performance and insulation.
[0017] According to the above steps, comparisons of different formulations are carried out, including the following comparison groups; Comparison group 1: Vulcanization temperature 200°C, die head temperature 200°C; Comparison group 2: Vulcanization time 3 minutes; Example group (the present invention): Vulcanization temperature 220°C, vulcanization time 5 minutes, die head temperature 220°C; Comparison group 1: Phase domain size > 100nm, heat aging retention rate 80%; Comparison group 2: Phase domain structure is uneven, embrittlement temperature -55°C; Example group: Phase domain size < 50nm, heat aging retention rate 92%, embrittlement temperature -65°C; Conclusion: Prolonging the vulcanization time and increasing the temperature promote microphase separation and improve performance.
[0018] The modification effect of nano-fillers is as follows: The grafting rate of KH-550 in modified nano-silica is 9% (measured by Si-C bond in XPS), and the grafting rate of unmodified nano-silica < 10%; The tensile properties of nano-fillers are compared as follows: Modified group 31MPa → Unmodified group 24MPa; The thermal conductivity of the montmorillonite composite is 4.2W / m·K (original MMT is only 1.8W / m-K); According to the above steps, extreme temperature tests are carried out on different comparison groups, including; Example group (150°C x 1000h): Elongation at break > 350%, tensile strength > 25MPa; Commercially available EPDM cable (150 °C x 1000 h): Elongation at break < 200% (failure); Example group (-70 °C): No cracks; Commercially available PVC cable (-70 °C): Brittle fracture.
[0019] Application of a high-temperature and low-temperature resistant elastic cable material in a cable, using any one kind of high-temperature and low-temperature resistant elastic cable material and a preparation method of a high-temperature and low-temperature resistant elastic cable material. The cable material is used to manufacture the sheath layer or insulation layer of a high-temperature and low-temperature resistant cable, and is suitable for high and low temperature environments in fields such as industrial robots, new energy vehicles, and polar scientific expeditions; The cable material forms a microphase separation structure through a dynamic vulcanization process, where the styrene block serves as a permanent physical crosslinking point, inhibiting the softening flow caused by chain segment migration, ensuring the structural stability of the cable under long-term operation scenarios at 150 - 200 °C, suitable for electric vehicle charging pile wire harnesses and wire harnesses at the joints of industrial robots. The antioxidant 1010 is compounded with the phosphite auxiliary antioxidant 168, and inhibits the molecular chain breakage induced by high-temperature oxidation through the dual mechanisms of hydroperoxide decomposition and free radical chain termination. The performance retention rate > 88% after thermal aging at 150 °C x 168 h; In Kraton G1650, a styrene-butadiene-styrene copolymer is blended with polyether TPU to form a multiphase elastomer network, where the proportion of the TPU soft segment is 25%, ensuring that the material does not crack under low-temperature impact at -70 °C, suitable for cables of polar scientific expedition equipment. The phosphite antioxidant 168 restricts the low-temperature crystallization trend of the polyether TPU molecular chain through free radical capture, maintaining the low-temperature resilience and elongation at break of the material; In the composition of the cable material, a composite antistatic agent and a montmorillonite complex are added to form a surface charge dissipation channel, reducing the surface resistance and preventing insulation failure caused by local electric field distortion.
[0020] The surface of the cable material has antistatic properties, and the antistatic performance of the cable material is improved by adding a composite antistatic agent.
[0021] Modified nano-silica is surface-grafted with polyacrylate through a silane coupling agent, and the grafting rate of the modified nano-silica ≥ 90%. The thickness of the hexagonal boron nitride nanosheets in the montmorillonite complex < 5 nm, the aspect ratio of the montmorillonite in the montmorillonite complex > 50. The hexagonal boron nitride nanosheets and montmorillonite are compounded by a mechanochemical method. The temperature of the screw in the extruder is gradually increased in sections, reducing the accumulation of shear heat and avoiding material thermal degradation. An on-line viscometer and a laser particle size analyzer are configured during the extrusion process of the extruder to provide real-time feedback on the fluidity and dispersion state of the material.
[0022] The modified nano-silica is grafted by silane coupling agent KH-550 in ethanol solvent. The mass ratio of KH-550 to silica is 1:5. After grafting, the modified nano-silica is dried at 60 °C to remove the solvent, and the grafting rate of the modified nano-silica is 290%; Hexagonal boron nitride nanosheets and sodium montmorillonite are mixed in a ratio of 2:3 and compounded by high-speed ball milling mechanochemical method. The particle size D50 < 1 μm and the dispersion is uniform.
[0023] In this scheme, it includes a blend network of styrene-butadiene-styrene block copolymer (SBS) and polyether TPU: The SBS hard segment (styrene block) serves as physical cross-linking points, forming a dynamic network structure with the TPU soft segment through hydrogen bonds, inhibiting the softening flow caused by chain segment migration. The proportion of the TPU soft segment (polyether group) is 25%, endowing the material with low-temperature resilience (brittleness temperature < -65 °C), and inhibiting the low-temperature crystallization trend through the free radical capture effect of phosphite antioxidant 168; Dynamic vulcanization process: At 220 °C / 8 MPa, the molecular chains of SBS and TPU form permanent chemical cross-linking points (microphase separation structure) through thiol-ene electrolytic reaction. The phase domain size < 50 nm (the control group > 100 nm), significantly improving the high-temperature stability (thermal aging retention rate 92% - 80% of the control group); Including the principle of optimizing the dynamic vulcanization process: Temperature gradient control: The temperature is raised in stages from 170 °C in zone 1 to 210 °C in zone 10, reducing the accumulation of shear heat (the melt temperature rise ≤ 15 °C), avoiding early cross-linking of the material. The die head pressure is 8 MPa, promoting the uniform dispersion of fillers and the full progress of cross-linking reaction, forming a stable microphase separation structure (TEM shows that the continuity of phase domains is increased by 40%); Including surface grafting of modified nano-silica to strengthen interfacial bonding: Grafting of KH-550 silane coupling agent: The surface amino / epoxy group modification of modified nano-silica is realized through the ethanol solvent method (grafting rate 90%), forming chemical bonding with the polyurethane soft segment (characteristic peak of Si-C bond measured by XPS), improving the uniform dispersion of fillers (D90 / D10 = 3.2 - 5.0 for the unmodified group), and the tensile strength after grafting increases from 24 MPa to 31 MPa (only 24 MPa for the control group), attributed to the increase in interfacial binding energy (from van der Waals force - chemical bond); Composite of hexagonal boron nitride nanosheets (h-BNNS) and sodium montmorillonite (MMT): h-BNNS (thickness < 5 nm) provides high thermal conductivity channels (thermal conductivity 4.2 W / m·K vs 1.8 W / m·K for the original MMT). MMT (aspect ratio > 50) is exfoliated to D50 < 1 μm through the interlayer swelling effect, forming a three-dimensional thermal conductivity network with h-BNNS, enabling the cable material to achieve rapid heat dissipation and extending the service life of the cable material; Microphase separation structure inhibits softening flow: Styrene blocks act as physical crosslinking points to restrict the migration of molecular chains (DSC shows no glass transition temperature drift); Dynamic vulcanization crosslinking density regulation: A die pressure of 8 MPa ensures an appropriate degree of crosslinking (gel content 35% - 40%) to avoid brittleness caused by excessive crosslinking; Optimization of the proportion of TPU soft segments: A 25% soft segment content provides sufficient free volume to inhibit crystallization (DSC confirms a crystallinity < 5%), and the elongation at break remains > 350% at -70°C; Free radical capture effect of antioxidant 168: Blocks the B - scission reaction initiated by free radicals at low temperatures (FTIR comparison confirms a 60% reduction in the intensity of the carbonyl peak); This cable material achieves breakthroughs in comprehensive performance in a wide temperature range (-70°C to 200°C), high anti - aging performance (performance retention rate of 92% at 150°C for 168 h), antistatic property, and high thermal conductivity (4.2 W / m·K) through multi - scale component design (SBS / TPU blend network, nano - filler modification), dynamic vulcanization process optimization, and the synergistic effect of the anti - aging system. The innovation of its principle is reflected in: the microphase separation structure inhibits softening flow, KH - 550 grafting improves dispersion and mechanical properties, the synergistic inhibition of aging by free radical capture and peroxide decomposition, and online monitoring and segmented temperature control improve stability. This technology breaks through the performance limit of traditional cable materials and is applicable to harsh working conditions such as electric vehicle charging piles and industrial robots.
[0024] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principle and spirit of the present invention.
Claims
1. A high-temperature and low-temperature resistant elastic cable material, characterized in that: It includes cable material, and the composition of the cable material contains Kraton G1650. The composition of the cable contains polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin 770, paraffin oil, and antioxidant 1010. The ratio of Kraton G1650, polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin 770, paraffin oil, and antioxidant 1010 is 35:25:3:2:0.5:15:0.
2.
2. A preparation method of a high-temperature and low-temperature resistant elastic cable material, using a high-temperature and low-temperature resistant elastic cable material as claimed in claim 1, characterized in that: It includes the following steps: Step 1, mixing; Step 2, extrusion; Step 3, vulcanization; Step 4, testing.
3. The preparation method of a high-temperature and low-temperature resistant elastic cable material according to claim 2, characterized in that: In Steps 1 to 4, more specifically: In the mixing step, except for the antioxidant, Kraton G1650, polyether TPU, modified nano-silica, montmorillonite complex, BASF Tinuvin 770, and paraffin oil are dried in a vacuum drying oven at 120°C for 4 hours to remove moisture and low-molecular volatile substances, and then mixed at room temperature for 15 minutes using a high-speed mixer to ensure nano-level uniform dispersion. The particle size distribution D90 / D10 ≤ 5 is detected by a laser particle size analyzer; In the extrusion step, the premixed material is added to the extruder. The temperature gradient of the 120mm twin-screw extruder is controlled as follows: from 170°C in zone 1 to 180°C in zone 2 to 190°C in zone one to 200°C in zones four to nine to 210°C in zone ten. The twin-screw rotation speed is 300 rpm, the length-diameter ratio L / D ≥ 48:1, the vacuum degree ≤ -0.09 MPa for devolatilization, the melt pressure is 5 - 10 MPa, the die head temperature is 220°C, and the residence time is 4 - 6 minutes; In the vulcanization step, a dynamic vulcanization process is implemented at the die orifice of the extruder. The vulcanization temperature is 220°C, the die orifice pressure is 8 MPa, and the residence time is 5 minutes to form a micro-phase separation structure; In the testing step, after forming, the cable material is granulated by water cutting or calendered by a granulator, and the performance is detected according to the following standards: Tensile properties: Detected by ASTM D412 - 22, and the test standards are: elongation at break > 350%, tensile strength > 28 MPa; Low-temperature brittleness: Detected by GB / T 2951.4, and the test standard is: embrittlement temperature < -50°C; Thermal aging performance: Detected by IEC 60216 - 1, and the test standard is: the performance retention rate > 88% after 150°C x 168 h; Electrical insulation performance: Detected by GB / T 3048 - 2007, and the test standard is: volume resistivity > 1014 Q·cm.
4. Application of a high-temperature and low-temperature resistant elastic cable material in a cable, using any one of the high-temperature and low-temperature resistant elastic cable materials in claims 1-3 and a preparation method of a high-temperature and low-temperature resistant elastic cable material, characterized in that: The cable material is used to manufacture the sheath layer or insulation layer of high-temperature and low-temperature resistant cables, and is suitable for high and low-temperature environments in fields such as industrial robots, new energy vehicles, and polar scientific research; The cable compound forms a microphase separation structure through a dynamic vulcanization process, where the styrene block serves as a permanent physical crosslinking point, inhibiting the softening flow caused by chain segment migration and ensuring the structural stability of the cable under long-term operation scenarios at 150 - 200 °C. It is applicable to the wire harnesses at the charging piles of electric vehicles and at the joints of industrial robot arms. The antioxidant 1010 is compounded with the phosphite auxiliary antioxidant 168, inhibiting the molecular chain breakage induced by high-temperature oxidation through a dual mechanism of hydroperoxide decomposition and free radical chain termination, and the property retention rate is >88% after thermal aging at 150 °C for 168 h; In Kraton G1650, a styrene-butadiene-styrene copolymer is blended with polyether TPU to form a multiphase elastomer network, where the proportion of the TPU soft segment is 25%, ensuring that the material does not crack under low-temperature impact at -70 °C. It is applicable to the cables of polar scientific research equipment. The phosphite antioxidant 168 restricts the low-temperature crystallization tendency of the polyether TPU molecular chain through free radical capture, maintaining the low-temperature resilience and elongation at break of the material; By adding a compound antistatic agent and a montmorillonite complex in the composition of the cable compound, a surface charge dissipation channel is formed, reducing the surface resistance and preventing insulation failure caused by local electric field distortion.
5. Use of a high-temperature and low-temperature resistant elastic cable material according to claim 4 in a cable, characterized in that: The surface of the cable compound has antistatic properties.
6. The preparation method of a high-temperature and low-temperature resistant elastic cable material according to claim 3, characterized in that: The modified nano-silica is surface-grafted with polyacrylate through a silane coupling agent. The grafting rate of the modified nano-silica is ≥90%. The thickness of the hexagonal boron nitride nanosheets in the montmorillonite complex is <5 nm, and the aspect ratio of the montmorillonite in the montmorillonite complex is >50. The hexagonal boron nitride nanosheets and montmorillonite are compounded by a mechanochemical method. The temperature of the screw in the extruder is gradually increased in sections, reducing the accumulation of shear heat and avoiding material thermal degradation. An on-line viscometer and a laser particle size analyzer are configured during the extrusion process of the extruder to provide real-time feedback on the fluidity and dispersion state of the material.
7. A method for preparing a high-temperature and low-temperature resistant elastic cable material according to claim 6, characterized in that: The modified nano-silica is grafted in an ethanol solvent through a silane coupling agent KH-550. The mass ratio of KH-550 to silica is 1:
5. After grafting, the modified nano-silica is dried at 60 °C to remove the solvent, and the grafting rate of the modified nano-silica is 290%; The hexagonal boron nitride nanosheets and sodium-based montmorillonite are mixed in a ratio of 2:3 and compounded by a mechanochemical method using a high-speed ball mill, with a particle size D50 < 1 μm and uniform dispersion.